Open Surgery for Extraction of an Embolized Pellet in the Middle Cerebral Artery From a Shotgun Injury. Issue 3 (13th November 2018) - Monterey, Michael; Kerr, Keith; Dannenbaum, Mark; Chen, Peng Roc; Blackburn, Spiros
Abstract: BACKGROUND AND IMPORTANCE: Embolization of shotgun pellet from the peripheral vasculature to the cerebral vessels has been a known phenomenon that has been reported previously in the literature. However, there is no consensus on clinical indications for intervention, best modality of intervention or management upon leaving the hospital. We describe a case of a shotgun pellet in the neck that embolized to the middle cerebral artery that was treated with open surgery. Discussed is the initial management on presentation, timing of intervention from surgery and detailed surgical technique. CLINICAL PRESENTATION: A 20-yr-old man presented after being shot at close range with a shotgun. He was neurologically intact on exam. Initial screening computed tomography (CT) of the brain noted a shotgun pellet in the region of the sylvian fissure without intracranial hemorrhage. Computed tomography angiography again displayed pellet in the vicinity of the left middle cerebral artery. He was emergently taken for an awake cerebral angiogram and subsequent surgical extraction of the shotgun pellet. CONCLUSION: Missile embolization of a bullet fragment to the intracranial vasculature is rare and requires difficult decisions regarding management. Critical factors that are to be considered prior to treatment include neurological clinical presentation, timing of the trauma, and anatomic location of injury. Patients who are without neurological deficit that display compromised blood flow require immediate cerebral angiogram followed by surgical intervention depending on location.